2015
DOI: 10.3168/jds.2014-8688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microencapsulated sodium butyrate in the close-up diet on performance of dairy cows in the early lactation period

Abstract: Two trials were conducted to determine the effect of sodium butyrate microencapsulated within triglyceride matrix (Na-butyrate) in the close-up period on performance of dairy cows and rumen papillae development. In trial 1, 26 Holstein-Friesian cows were randomly allocated to 2 groups (13 cows/group) and fed prepartum a total mixed ration (TMR) without or with 300g of Na-butyrate/d from 30 d before expecting calving to parturition. After calving, the same lactational TMR without Na-butyrate was offered to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 24 publications
4
36
2
Order By: Relevance
“…In the current study, molar proportions of both acetate and propionate remained fairly constant, suggesting that the amount of butyrate added by TB had no effect on the fermentation pattern of the basal diet, and the present results are consistent with reports by Kowalski et al. (). However, we observed increased butyrate molar proportion in the rumen of ewes fed TB, and this might be caused by the elevated ruminal butyrate concentration.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, molar proportions of both acetate and propionate remained fairly constant, suggesting that the amount of butyrate added by TB had no effect on the fermentation pattern of the basal diet, and the present results are consistent with reports by Kowalski et al. (). However, we observed increased butyrate molar proportion in the rumen of ewes fed TB, and this might be caused by the elevated ruminal butyrate concentration.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study by Kowalski et al. () reported that DMI was not affected when sodium butyrate was included in the diet for bulls. In the current study, TB as feed additive was added in the experimental diets; it may have modified the taste and that might have resulted in greater refusals by the TB‐supplemented ewes, although TB is stable and less odorous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All major VFA promote rumen papillae development in vivo (Sutton et al, 1963;, but Bu is generally believed to have a particular proliferative effect Malhi et al, 2013;Kowalski et al, 2015). Given the greater papillae surface area in early lactation (16, 30, and 44 d pp) associated with a rapid compared with a gradual increase in concentrate allowance , it was expected that Bu production would be larger at 16 and possibly 44 d pp in RAP compared with GRAD.…”
Section: Vfa Productionmentioning
confidence: 99%
“…Often, Bu is credited with special proliferative properties and is frequently used in treatments in rumen studies Malhi et al, 2013;Kowalski et al, 2015). Papers on the special proliferative effects of Bu often refer to the work of .…”
Section: Vfa Driving Rumen Morphological Adaptationmentioning
confidence: 99%